Identification of Bioactive Compounds and α-Glucosidase Inhibition Activity of Caesalpinia bonduc Seed Extract In vitro - Oczhinvia Dwitasari; Djarot Sasongko Hami Seno; Mega Safithri (Current Biochemistry, 2018)
This study is aimed for finding alternative ways to treat diabetes. Many studies have beendone before, but focused on identification of α-glucosidase inhibition mechanism. This study wasconducted by extracting Caesalpinia bonduc seed using two methods maceration by ethanol 96%and the others boil by water. The ethanol extract was then fractioned into three fractions, n-hexane,ethyl acetate, and ethanol. To find the bioactive compounds, the ethanol extract was then tested byseveral phytochemistry tests. The phytochemistry test showed positive results for alkaloid, flavonoid,saponin and triterpenoid. The inhibition mechanism was tested using pNPG. The inhibition testshown that the mechanism was a competitive inhibition, by the Dixon plot. The calculated inhibitionconcentrations for 50% substrate (IC50) for ethyl acetate fraction are 1655.8079 μg/ml for 5 mMsubstrate and 803.9521 μg/ml for 10 mM substrate. From the results of this study, we concluded thatthe extract of Caesalpinia bonduc has inhibition activity toward α-glucosidase enzyme. Keywords: α-glucosidase inhibition, Caesalpinia bonduc seed extract, diabetes treatment